Diversity And Some Aspects Of Biology Of Ephemeroptera In Streams Of Royal Belum State Park In Perak - Ghani, Wan Mohd. Hafezul Wan Abdul (2012)
Communities of Ephemeroptera (mayflies) investigated in four rivers; Kejar River, Tan Hain River, Mes River and Ruok River of Royal Belum State Park (RBSP) were found to be relatively diverse (H’ = 1.407 – 2.166). Twenty genera of 10 families were represented by 10308 individuals collected by the kick sampling technique from February 2009 until February 2010. Among the four rivers, Tan Hain River had the highest abundance (3542) and although Ruok River had the lowest abundance (1500), it scored the highest Diversity Index (H’ = 2.166, 1-D = 0.839) and Richness Index (R1= 2.325, R2 = 0.465). Baetis sp. was dominant in all rivers with an average density of 651.11 individuals m-2 followed by Habrophlebiodes sp. (Leptophlebiidae) of 187.76 individuals m-2. Cinygmula sp., Drunella sp. and Teloganella sp. were rare. Most ephemeropterans collected in all rivers were collector-gatherers; collector-filterers were scarce and scrapers and predators were uncommon. The scores of Water Quality Index (WQI) classified all rivers into Class I of very clean water quality. All environmental parameters were weakly associate with the abundances of ephemeropteran species (Spearman’s rho < 0.3, P=0.05) except the Chemical Oxygen Demand (COD). The head width-body length scatter plots of Baetis sp. separated the nymphal stages into 9 instars (F-F-8). Its life cycle took approximately a month from the youngest instar to the final instar. Adult emergence took place every month, thus Baetis sp. is speculated to have a multivoltine life history in both Tan Hain and Mes rivers.